PEMANFAATAN SOSIAL MEDIA INSTAGRAM SEBAGAI STRATEGI MARKETING BRAND IMAGE PROPER SHINE DIKOTA PEKANBARU - Haryadi, Yoandi; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Many instagram user among online business are trying to utilize instagram as a means of supporting bussiness promotion. One of them Proper Shine Detailing utilizing instagram as social media marketing them to be able to assist the formation of brand image in the community in the city of Pekanbaru. The purpose of the research is to know the strategy to build relationship, brand building strategy and promotion strategy especially consumer of service user of Proper Shine Detailling in the city of Pekanbaru.In this study the authors used a qualitative descriptive method with data collection techniques through observation and interviews. Information in thia study were 10 people who where taken by purposive sampling technique, those are Proper Shine Detailing owner, 3 employees Proper Shine Detailing, and 6 Proper Shine Detailing customers who use instagram.The results showed that the strategy of build up customer realetionships in shaping of The Proper Shine Detailing brand image by doing a maximum service. The next strategy to build a brand in shaping the brand image by educating the importance of caring the vehicles periodically. And the last strategy for the promotion is by posting the final detailinf on social media, such as instagram.Key word : brand image, strategy to build relationship brand building strategy and promotion strategy